2014
DOI: 10.1175/waf-d-13-00126.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Real-Time Tornado Information Disseminated through NWS Products

Abstract: Real-time confirmation of a tornado specified in National Weather Service (NWS) warnings and statements is believed to increase the credibility and urgency of these critical warning messages for the end user, because it represents the greatest degree of certainty that the hazard exists. This timely tornado information disseminated in official NWS products and relayed through multiple sources by private and public partners may help the public believe, personalize, confirm, and respond to the warning message. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…15). 1) real-time comparison of available observations with the model-based estimates of the storm environment, 2) real-time monitoring of storm structure and rotational characteristics via WSR-88D sampling, and 3) supporting evidence of a tornado via the development of a dual-polarization tornadic debris signature (DPTDS; e.g., Bodine et al 2013;Schultz et al 2012a,b; Bunkers and Baxter 2011) with vertical and temporal continuity, since a majority of tornadoes are not reported to local National Weather Service offices in real time (Blair and Leighton 2014). 13.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15). 1) real-time comparison of available observations with the model-based estimates of the storm environment, 2) real-time monitoring of storm structure and rotational characteristics via WSR-88D sampling, and 3) supporting evidence of a tornado via the development of a dual-polarization tornadic debris signature (DPTDS; e.g., Bodine et al 2013;Schultz et al 2012a,b; Bunkers and Baxter 2011) with vertical and temporal continuity, since a majority of tornadoes are not reported to local National Weather Service offices in real time (Blair and Leighton 2014). 13.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Newman et al (2013) found utility in applying range correction to the local, linear least squares derivatives (LLSDs; Smith and Elmore 2004) azimuthal shear algorithm, and this procedure aided in differentiating between nontornadic and tornadic radar scans for a small number of events. Blair and Leighton (2014) noted the need for robust, scientific guidance for real-time tornado intensity estimates in their assessment of event confirmation in NWS warnings and statements across the central continental United States (CONUS) from 2007 to 2011. The early studies investigating the relationship between tornado intensity and radar (e.g., Kingfield et al 2012;LaDue et al 2012;Toth et al 2013) have shown some ability to identify different levels of tornado intensity in a diagnostic manner, thereby lending credence to the underlying idea of tornado intensity identification, from which IBW is based.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, given a sufficiently short distance and clear line of sight between the radar and the tornado, identification of existing tornadoes in Doppler weather radar data is nearly ubiquitous. The TVS and TDS serve as useful tornado proxies both for forecasters issuing warnings (e.g., Blair and Leighton 2014) and for researchers conducting observational studies (e.g., Trapp et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Last, a TDS often persists for a significant time after tornado demise, which makes sense given observations of long-range debris transport (e.g., Magsig and Snow 1998). Even with these limitations, the TDS remains a good indicator of lofted debris and is especially useful in the absence of a spotter network (e.g., Blair and Leighton 2014).…”
Section: Introductionmentioning
confidence: 99%